ChemInform Abstract: Two New 3‐D Boratopolyoxovanadate Architectures Based on the [V12B16O50(OH)8]12‐ Cluster with Different Metal Linkers. Issue 13 (1st April 2014) - Liu, Xing; Zhou, Jian; Xiao, Hong‐Ping; Kong, Chunyang; Zou, Huahong; Tang, Qiuling; Li, Jianhui
Abstract Compounds (IV) and (VI) are characterized by single crystal XRD.